КУРАШ БИЛАН ШУҒУЛЛАНУВЧИ ТАЛАБАЛАРНИ БОШЛАНҒИЧ БОСҚИЧДА ТЕХНИК ҲАРАКАТЛАРГА ЎРГАТИШ АСОСЛАРИ - Келдиёров, Ш.Э. (SCIENCE and SOCIETY, 2018)
The article is devoted to the description of the main technical actions of a fighter at the primary stage of training, special attention is paid to the study of technical devices in parts and in whole. It is emphasized that the technical devices taught at the primary stage remain throughout the whole sport activity of a sportsman, it’s difficult to retrain them again.